2006
DOI: 10.1128/cvi.13.3.376-379.2006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Peripheral Blood Lymphocyte Subsets in Patients with AcutePlasmodium falciparumandP. vivaxMalaria Infections at Wonji Sugar Estate, Ethiopia

Abstract: We investigated the absolute counts of CD4 ؉ , CD8 ؉ , B, NK, and CD3؉ cells and total lymphocytes in patients with acute Plasmodium falciparum and Plasmodium vivax malaria. Three-color flow cytometry was used for enumerating the immune cells. After slide smears were stained with 3% Giemsa stain, parasite species were detected using light microscopy. Data were analyzed using STATA and SPSS software. A total of 204 adults of both sexes (age, >15 years) were included in the study. One hundred fifty-eight were ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
60
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 28 publications
16
60
1
Order By: Relevance
“…Nevertheless, cell-mediated response seems unaffected as evidenced in studies during the convalescent period in P. vivax-infected hosts, thus confirming a T cell-specific response, which was also reactive to P. falciparum antigens [104,107].…”
Section: Specific Antimalarial Immunity During Pregnancysupporting
confidence: 54%
“…Nevertheless, cell-mediated response seems unaffected as evidenced in studies during the convalescent period in P. vivax-infected hosts, thus confirming a T cell-specific response, which was also reactive to P. falciparum antigens [104,107].…”
Section: Specific Antimalarial Immunity During Pregnancysupporting
confidence: 54%
“…Depletion of CD4 + T cells is a common consequence of HIV-1 infection (Grossman et al 2002). However, acute malaria only also reduces the number CD4 + T lymphocytes (Chougnet et al 1992, Kassa et al 2006. Among the patients evaluated in this study, the lowest CD4 + T values were observed in the co-infected patients.…”
Section: Discussionmentioning
confidence: 67%
“…These results suggest a heightened degree of immunosuppression in malaria-associated HIV-1/AIDS. Interestingly, this reduction in CD4 + T cells is transient and the levels of these cells increase after successful antimalarial therapy, although the number of CD4 + T cells does not reach the previous counts (Kassa et al 2006, Van Geertruyden et al 2006a. Therefore, each episode of acute malaria causes an excess decrease in the CD4 + T cell numbers (Mermim et al 2006), which aggravates the immunosuppressed state.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between micronuclei frequency and apoptosis has been reported as directly proportional; i.e., under conditions of reduced apoptosis, micronucleus formation was also reduced [4]. Induction of apoptosis has been observed during P. falciparum infection in human lymphocytes, endothelial cells, hepatocytes and neurons [10][11][12]. It may also be the cause of lymphopaenia which occurs in the course of malaria because acute malaria infection causes a depletion of lymphocyte populations in the peripheral blood [13,4].…”
Section: Discussionmentioning
confidence: 99%